Roy Scranton, Learning to Die in the Anthropocene: Reflections on the End of a Civilization - Foster, John (Journal for the Study of Religion, Nature and Culture, 2018)
Roy Scranton, Learning to Die in the Anthropocene: Reflections on the End of a Civilization (San Francisco, CA: City Lights Books, 2015), 142pp., $13.95 (pbk), ISBN: 978-0-87286-669-0.